Investigation of the survival characteristics of Rhodococcus coprophilus and certain fecal indicator bacteria. - Oragui, J I (1983)
Rhodococcus coprophilus and Clostridium perfringens survived in fresh water samples held at 5, 20, and 30 degrees C for over 17 weeks, whereas Escherichia coli and fecal streptococci disappeared after 5 weeks at all three temperatures. R. coprophilus survived for more than 8 months in sterilized sewage and deionized water at all three temperatures, whereas in normal sewage held at 20 degrees C, the survival time was 12 to 26 weeks. In samples held at 30 degrees C, survival times were shorter, probably because of interbacterial competition or protozoal predation. The results indicate that R. coprophilus may be a useful indicator of the presence of remote fecal pollution of farm animal origin, but not of recent pollution, when enumerated alone in polluted waters or wastewaters.